ANALISIS PROGRAM KEGIATAN KEAGAMAAN TERHADAP PENINGKATAN AKHLAK SISWA (STUDI KASUS MTsN KOTA BOGOR) - Wanti Rahayu; Retno Triwoelandari; Syarifah Gustiawati (Universitas Pakuan, 2019)
This study aims (1) to determine the religious activity program (2) to find out the implementation of religious activities (3) to determine the impact of religious activities on improving the morality of students in the MTsN of Bogor city. Methodologically this research uses qualitative descriptive approach which is descriptive and not numerical or a research method that describes data so that accurate data can be obtained. Data collection techniques in this study are using observation,interviews, documentation and triangulation. Data analysis techniques are reducing, presenting and drawing conclusions from research results. The results of this study that the religious activity program in MTsN in the city of Bogor is included in the good category, this is evidenced by the many programs of religious activities in the city MTsN in Bogor that are in accordance with the specified religious programs, namely reading the Quranic verses bertadarus before entering the lesson hours for 10 minutes, pray at the beginning and at the end of the lesson, dhuha prayer at rest, zuhur prayer in congregation, zikir together, get used to on Friday, every Friday students wear Muslim clothing, tahfidz quran, held a pesantren kilat in the month of Ramadan, the celebration of the Islamic Great Day, and students are enthusiastic in carrying out religious activity programs and most of them claim to be happy with the religious activity programs, and the impact of the religious activities of Bogor city MTsN on improving student morals, which can make students more obedient in worship, always read the Quran every day, add religious insight and make students better themselves.